Die Flächeninanspruchnahme in Deutschland im Vergleich mit der Situation in England - Haaren, Christina von; Nadine, Vincent (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
A comparison of the differences in land consumption in England and Germany as well as an analysis of the general conditions of the English planning system show how blatant the differences between the two industrial countries are and deliver the initial explanations for the differences. In the year 2001, 40ha/year/100,000 residents were consumed in Germany (not considering recreational areas). In contrast, the corresponding statistic in England was merely 12.7 ha. The essential reasons for the success of the English system in this area of policy making seems to lie in: the English planning system, the emphasis of recycling unused plots of land within towns and the preservation of “Green Belts” as well as the English taxation system. The English example gives reason to once again contemplate the relatively high strength of community planning interests in German spatial planning. Also without major changes in the planning system, measures such as the reduction of economic incentives that promote land consumption and the further development of concepts for tradable land use permits in connection/cooperation/combination with spatial planning.